О ментальном значении сакрализации пространства византийского Херсона - Сорочан, С.Б. (My University, 2017)
The article attempts to raise the issue of the mental meaning of sacred, religious monuments which existed in the Byzantine Cherson. Most of them belong to 6th – 10th centuries. As well as in Byzantium, for contemporaries they had a significance not only revered shrines, but they also represented an important cultural code of society, a kind of protective field of celestial forces. These religious monuments were “repeaters” of such holiness which extended itself to the whole territory of the empire. This important point of public consciousness explains why during the construction of such facilities sometimes Romans donated their own real comforts in favor of spiritual creativity.